Electronic acquisition of OSCE performance using tablets - Hochlehnert, Achim (GMS Z Med Ausbild, 2015)
Background: Objective Structured Clinical Examinations (OSCEs) often involve a considerable amount of resources in terms of materials and organization since the scores are often recorded on paper. Computer-assisted administration is an alternative with which the need for material resources can be reduced. In particular, the use of tablets seems sensible because these are easy to transport and flexible to use. Aim: User acceptance concerning the use of tablets during OSCEs has not yet been extensively investigated. The aim of this study was to evaluate tablet-based OSCEs from the perspective of the user (examiner) and the student examinee. Method: For two OSCEs in Internal Medicine at the University of Heidelberg, user acceptance was analyzed regarding tablet-based administration (satisfaction with functionality) and the subjective amount of effort as perceived by the examiners. Standardized questionnaires and semi-standardized interviews were conducted (complete survey of all participating examiners). In addition, for one OSCE, the subjective evaluation of this mode of assessment was gathered from a random sample of participating students in semi-standardized interviews. Results: Overall, the examiners were very satisfied with using tablets during the assessment. The subjective amount of effort to use the tablet was found on average to be “hardly difficult”. The examiners identified the advantages of this mode of administration as being in particular the ease of use and low rate of error. During the interviews of the examinees, acceptance for the use of tablets during the assessment was also detected. Discussion: Overall, it was found that the use of tablets during OSCEs was well accepted by both examiners and examinees. We expect that this mode of assessment also offers advantages regarding assessment documentation, use of resources, and rate of error in comparison with paper-based assessments; all of these aspects should be followed up on in further studies.